Reliability and validity of the Bladder and Bowel Dysfunction Questionnaire among Turkish children - AY, NADİYE PINAR (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2017)
Background/aim: We developed a Turkish version of the Bladder and Bowel Dysfunction Questionnaire (BBDQ) and evaluated its psychometric properties among Turkish pediatric patients. Materials and methods: The BBDQ was translated into Turkish and then it was back-translated into English. A total of 193 patients were asked to complete the Turkish version of the BBDQ as well as the Dysfunctional Voiding and Incontinence Scoring System (DVISS). In addition, 39 children completed the same questionnaires twice at 2-week intervals for test-retest evaluation. Results: Cronbach's alpha coefficient of the BBDQ was 0.727. Reliability of the test/retest was 0.759 (P < 0.001). Area under the curve of the receiver operating characteristic plot was 0.765. There were statistically significant differences in BBDQ scores between the controls and patients (P < 0.001). Analysis demonstrated moderate convergent validity against the DVISS (r: 0.78, r(2): 0.601, P < 0.0001). Conclusion: The Turkish version of the BBDQ is a reliable and valid instrument for Turkish pediatric patients with bladder and bowel dysfunction in clinical and research settings.
Keywords: Bladder bowel dysfunction; pediatric urology; questionnaire; Turkish validation; URINARY-TRACT-INFECTION; VOIDING SYMPTOM SCORE; VESICOURETERAL REFLUX; STANDARDIZATION COMMITTEE; CONTINENCE-SOCIETY; FUNCTIONAL CONSTIPATION; TERMINOLOGY; ADOLESCENTS; SYSTEM